Herbivorous mammals as seed dispersers in a Mediterranean dehesa - Malo, Juan E; Suárez, Francisco (Oecologia, 1995)
Endozoochorous seed dispersal by herbivo- rous mammals has been verified repeatedly and its possi- ble influence on the structure and function of herbaceous communities has been suggested. Quantitative studies, however, are lacking in the field of seed dispersal via the dung of herbivore guilds in little-altered environments. The present paper analyses seed dispersal via rabbit, fal- low deer, red deer and cow dung in a Mediterranean de- hesa (open woodland used for hunting and ranching) during the seeding season. Dung seed content was deter- mined by the glasshouse cultivation of eight dung sam- ples from each herbivore, collected fortnightly between February and August. The four herbivores disperse many seeds (spring averages are 6-15 seeds per gram of dry dung and maxima of 25-70) from a large number of spe- cies (totals between 52 and 78). Dispersal seems to be mainly determined by seed production of the plant com- munity. This is reflected in (i) the dissemination of a high percentage of the species present in the dehesa, (ii) great seasonal variability, related to seed production, in the amount of seeds and number of species dispersed, and (iii) a high semi-quantitative similarity of seed con- tent in the four types of herbivore dung throughout the year. There is also important quantitative variation that depends on animal traits and feeding habits. These re- sults and the characteristics of species found in dung suggest the adaptation of plant species to the dispersal of their seeds via herbivore gut. This process may well have profound implications for vegetation dynamics and the evolution of plant traits.
Keywords: endozoochory; mediterranean grasslands; pasture dynamics; seed dispersal; Therophytes